Pengembangan Modul Biotesitik Pencemaran Lingkungan Untuk Meningkatkan Nilai Karakter Religius Dan Peduli Lingkungan - Muhamad Majdi; Usep Soetisna; Wahidin Wahidin (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
This research is motivated by sense of knowing from researcher about the feasibility of biological materials used in Madrasah Aliyah. Learning Objectives MANU Putri Buntet Pesantren Cirebon focuses on achieving the vision and realizing the mission. Based on the results of observation of learning and interviews with biology teachers, it was found that to support the achievement of learning objectives in MANU Putri Buntet Pesantren Kabupaten Cirebon required instructional materials designed with attention to the characteristics and needs of students according to the characteristics of the school. This research uses research and development method about instructional system approach. The research procedure includes five major stages of instructional design development as analysis, design, development, implementation, and evaluation. Products of research and development in the form of Bioteistik module. Bioteistic module teaching materials have been validated and obtained an average score of 79.17% falling within the eligible category. Bioteistic Implementation. Bioteistic modules have been validated and gained in learning significantly optimizing the internalization aspects of students' attitude values. Internalization of religious and environmental values of each observation 96,43% and 82.97 % and 81.68 % are both categorized as entrenched. Implementation of Bioteistic Module at MANU Putri Buntet Pesantren  Cirebon get positive response from teachers and students. This study shows that the Bioteistic module teaching materials are feasible to be implemented and effective in optimizing student learning outcomes especially in the affective domainKeywords: Module; Bioteistik; Value of Religious Character; Caring Environmental;